T008 rTMS in depression – Is more always better?. Issue 3 (March 2017) - Fitzgerald, P.
Abstract : Question: Repetitive transcranial magnetic stimulation (rTMS) is now a well-established new treatment modality for patients with depressive disorders that has been assessed across a large range of controlled studies. However, limited research has explored the basic parameters used in the design of rTMS treatment protocols especially in regards to variables determining the dose of treatment. Over time, dose has generally increased without the impact of this being systematically assessed. Therefore, we have been exploring aspects of treatment dose and how they relate to treatment outcomes. Methods: We have conducted several studies designed to address rTMS dose related issues. First, we have conducted several studies using TMS-EEG and TMS-NIRS methods to explore the effects of stimulation at increasing intensities on the prefrontal cortex. Second, we have conducted a large multi-site trial investigating the effect of pulse number as a dose variable on clinical response to rTMS in depression. Results: TMS-NIRS studies have indicated that there is a clearly bimodal response to increasing TMS stimulation intensity which is likely to have implications for the determination of optimal dosing for clinical outcomes. Our randomised controlled data do not suggest that increasing pulse number in an rTMS treatment protocol above standard levels is associated with improved outcomes. Conclusions: Improvements in the application of rTMS treatment are likely to be possible but 'more does not always seem to be better'. Improved outcomes may be achieved but optimising stimulation intensity but not increasing pulse number in individual treatment sessions.